PENGARUH PEMBELAJARAN SOCIAL INTERACTION MODEL TERHADAP HASIL BELAJAR PESERTA DIDIK DI SMA NEGERI 2 BATANG KAPAS, PESISIR SELATAN - Febri, Nadila Valentina; Mariya, Sri (JURNAL BUANA, 2023)
This study aims to see the effect of learning social interaction models on student learning outcomes at SMA Negeri 2 Batang Kapas, Pesisir Selatan. The design used in this study is quantitative with a quasi-experimental research type. The sampling technique used in this study was total sampling with a sample size of 62 people. Data analysis in this study used SPSS 26. Data collection techniques in the form of interviews, documentation, and learning outcomes tests were using pretest and posttest. Data processing in this study used normality test, homogeneity test and T test to determine the hypothesis. The results of the study prove that there is a significant effect between the experimental class and the kontrol class. Calculation of the average, the experimental class got a result of 81.90 and the kontrol class got a result of 77.03. Analysis of the effectiveness using N-Gain, obtained the results of the effective of the experimental class 67% with information quite effective to be applied while in the kontrol class obtained the results of effective of 54% with information less effective to be applied.